Land use and climate change implications for biodiversity and habitat loss within the public and private reserves of the Southern Waterberg district, Limpopo - Archer, Emma (University of Pretoria, 2024)
Mini Dissertation (MSc (Environmental Management))--University of Pretoria, 2024.